PERAN BUMDES DALAM PEMBERDAYAAN MASYARAKAT DI DESA JATISURA KECAMATAN CIKEDUNG KABUPATEN INDRAMAYU - Nur Hamid; Nova Indriyanti; Agus Riyadi (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
BUMDES is a village business institution managed by the community and village government to strengthen the village economy and build community social cohesion based on the needs and potential of the village. The Jatisura village government has established the Surakarya BUMDES as an institution for the welfare of the community's economy. It follows the role of the Surakarya BUMDES in empowering the community in Jatisura village. Surakarya BUMDES is a business entity whose entire or most of the capital is owned by the village through direct participation in village wealth, assets, services, and for the greatest prosperity of the village people. The problems in this study are 1) how is the role of the Surakarya BUMDES in empowering the community through processed mango fruit crafts in Jatisura village, Cikedung sub-district, Indramayu District. 2) How is the community empowerment model through Surakarya BUMDES in Jatisura village, Cikedung sub-district, Indramayu District. This study uses a descriptive qualitative method with a phenomenological approach with data collection techniques through observation, interviews, and documentation. The results of this study indicate that the role of Surakarya BUMDES in community empowerment is 1) Development and development of the economic potential and capacity of the community, 2) active efforts to improve the quality of human and community life, 3) supporting the community in realizing and developing the economy of rural communities, 4) and Helping the community to increase their income. The empowerment model carried out by the Surakarya BUMDES in Jatisura village uses a community development and participatory model. The community development model exists in the Bumdes of Jatisura village by developing the potential of natural resources to be processed into processed mangoes. Participatory empowerment model in Surakarya BUMDES with mango processing training from Surakarya BUMDES. The empowerment model approach used is top-down; the government budget determines the success of this empowerment.